A policy-making model for evolutionary SME behavior during a pandemic recession supported on game theory approach. (March 2023) - Hafezalkotob, Ashkan; Nersesian, Lia; Fardi, Keyvan
Highlights: We consider labor-based and production-based government policies to face the crises. An evolutionary game theoretic model is used to study the behavior of SMEs. The suitable policies can help to prevent SMEs from bankruptcy during crisis. The policies require different amounts of time to affect the SMEs strategies. Social welfare & government expenditure are key evaluation factors for the policies. Abstract: The global economy has experienced a tremendous shock caused by the Covid-19 pandemic and its effects on the normal activities of SMEs, which provide essential driving economic force. Considering that there is currently no precise prediction about the end of this pandemic, many SMEs must make critical decisions about whether to remain in the market during the pandemic or to leave it, investing their assets in a more secure sector of the economy. However, in order to convince SMEs to remain in the market, thus maintaining the damaged economy, governments may variously apply punitive or supportive measures. In this regard, the interaction between SMEs strategies and government measures can be considered as an evolutionary game, in which the governments impose various policies after observing the evolutionary behaviors of SMEs. An evolutionary stable strategy (ESS) is derived through a replicator dynamic system, and the available payoff of each player is calculated by Nash equilibrium (NA). Finally, a numerical example is presented, and related managerial insights are proposed at the end of the current study. For instance, contrary to general belief, it can be inferred from investigating possible scenarios that punitive policies are more effective than supportive measures in convincing SMEs to remain in the market.